A clathrin light chain: a reporter mouse for in vivo imaging of endocytosis - Grimm, Elisabeth; Hoeven, Franciscus van der; Sardella, Donato; Willig, Katrin I.; Engel, Ulrike; Veits, Nisha; Engel, Robert; Cavalcanti-Adam, Elisabetta A.; Bestvater, Felix; Bordoni, Luca; Jennemann, Richard; Schönig, Kai; et al. (PLOS ONE, 2022)
Clathrin-mediated endocytosis (CME) is one of the best studied cellular uptake pathways and its contributions to nutrient uptake, receptor signaling, and maintenance of the lipid membrane homeostasis have been already elucidated. Today, we still have a lack of understanding how the different components of this pathway cooperate dynamically in vivo. Therefore, we generated a reporter mouse model for CME by fusing eGFP endogenously in frame to clathrin light chain a (Clta) to track endocytosis in living mice. The fusion protein is expressed in all tissues, but in a cell specific manner, and can be visualized using fluorescence microscopy. Recruitment to nanobeads recorded by TIRF microscopy validated the functionality of the Clta-eGFP reporter. With this reporter model we were able to track the dynamics of Alexa594-BSA uptake in kidneys of anesthetized mice using intravital 2-photon microscopy. This reporter mouse model is not only a suitable and powerful tool to track CME in vivo in genetic or disease mouse models it can also help to shed light into the differential roles of the two clathrin light chain isoforms in health and disease.